Duality in Linear Programming Problems Related to Deterministic Long Run Average Problems of Optimal Control - Finlay, Luke; Gaitsgory, Vladimir; Lebedev, Ivan (SIAM journal on control and optimization, 2008)
It has been established recently that, under mild conditions, deterministic long run average problems of optimal control are "asymptotically equivalent" to infinite-dimensional linear programming problems (LPPs) and that these LPPs can be approximated by finite-dimensional LPPs. In this paper we introduce the corresponding infinite- and finite-dimensional dual problems and study duality relationships. We also investigate the possibility of using solutions of finite-dimensional LPPs and their duals for numerical construction of the optimal controls in periodic optimization problems. The construction is illustrated with a numerical example.